Best Answer

x3 + ax + 3a + 3x2 = x (x2 + a) + 3 (a + x2) = x (x2 + a) + 3 (x2 + a) = (x2 + a)(x + 3) Checking the work: x3 + ax + 3x2 + 3a or x3 + 3x2 + 3a + ax = x2 (x + 3) + a (3 + x) = x2 (x + 3) + a (x + 3) = (x + 3)(x2 + a)

Study guides

☆☆

Q: What is a grouping factor for polynomial x3 ax 3a 3x2?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

(a - 2)(b + 3)

x^3 + ax + 3a + 3x^2 = (x^3 + 3x^2) + (ax + 3a) = x^2(x + 3) + a(x + 3) = (x + 3)(x^2 + a)

The GCF is 3a

15

2a(3a - 4b + 1)

Related questions

(a - 2)(b + 3)

It is: 3a(1-4b)

The factors of 3a are 3 and a.

Since 3a is a factor of 6ab, it is automatically the GCF.

The greatest common factor (GCF) of 2a and 3a is a.

(3a + b)(3a - b)

You would factor 3a + 9b as: 3(a+3b)

3a(2a + 1)

3a - 5 cannot be factored further.

-3(a^2 - 3a + 7)

If that's 9a2, the answer is a(a2 - 9a + 3) x(5x2 + 3x - 1) -8d(d2 + 3d + 1)

Yes.